2021
DOI: 10.1111/ejn.15493
|View full text |Cite
|
Sign up to set email alerts
|

Irisin injection mimics exercise effects on the brain proteome

Abstract: Physical inactivity can endanger human health and increase the incidence of neurodegenerative disease. Exercise has tremendous beneficial effects on brain health and cognitive function, especially in older adults. It also improves brain-related outcomes in depression, epilepsy and neurodegenerative disorders, such as Parkinson's disease and Alzheimer's disease. Irisin is a mediator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 125 publications
2
8
0
Order By: Relevance
“…A novelty of this study was that irisin was directly administered to the studied PD model rather than induced by exercise. A previous study in mice implementing cellular pathway analysis showed that irisin injection has similar effects with exercise on brain proteome [ 51 ] supporting the idea that irisin administration could be used instead of exercise when the latter is not feasible.…”
mentioning
confidence: 69%
“…A novelty of this study was that irisin was directly administered to the studied PD model rather than induced by exercise. A previous study in mice implementing cellular pathway analysis showed that irisin injection has similar effects with exercise on brain proteome [ 51 ] supporting the idea that irisin administration could be used instead of exercise when the latter is not feasible.…”
mentioning
confidence: 69%
“…Physical activity has beneficial effects on brain health and cognitive functions. Furthermore, it is known that physical activity has protective effects against neurodegenerative diseases and improves the symptoms (37). Physical exercise is recommended as an alternative treatment to reduce epileptiform discharges and seizure frequency, to increase cardiorespiratory fitness and muscle strength, and to provide better health conditions (38).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the role of irisin in PD, irisin was peripherally delivered before or after the establishment of MPTP treated mice to explore its effect on neuroprotection and treatment (Fig. 1a, m), in which irisin injection dose was the median dose reported in literature 13,17,20,22,23,[25][26][27][28][29] . To evaluate the effect of irisin in MPTPinduced motor disfunction, we evaluated behavioral tests in mice.…”
Section: Peripherally Delivered Irisin Improves Motor Function and Do...mentioning
confidence: 99%
“…Irisin contains 112 amino acids, is heavily glycosylated and is 100% conserved between mouse and human 11 , 12 . Currently, irisin could be regarded as an extremely promising myokine since the effect of peripheral irisin injection in mice was very similar to that led by endurance exercise 13 , and exercise has been proposed as a non-pharmacological management for people who are in the early stages of PD or people who are experiencing balance or motor function problems 14 , 15 . The structure of irisin and its elevation with endurance exercise in humans has been confirmed using tandem mass spectrometry of human plasma 16 .…”
Section: Introductionmentioning
confidence: 99%